Parents' Perceptions and Preferences Toward School Selection for Elementary School-Age Children - Kayla Hajar Zahira; Wahdan Najib Habiby (MASI Mandiri Edukasi, 2025)
Children's education is the main responsibility of parents as the initial foundation for shaping children's character and intelligence. This study analyzes parents’ perceptions and preferences in selecting schools for elementary-age children. The research employed a quantitative descriptive approach using a survey method involving 112 parents of elementary school-aged children. Data were analyzed using descriptive statistics and cross-tabulation with the Statistical Package for the Social Sciences (SPSS). The findings indicate that parental decisions are influenced by their perceptions, which are shaped by factors such as educational background, personal experience, and income. In contrast, preferences tend toward factors like school facilities, safety, a conducive learning environment, technology integration, religious education, leadership, academic performance, and location. The characteristics of the respondents also affect their school selection behavior. These results help explain the declining interest in public schools in certain areas. This study contributes to a better understanding of how parental decision-making may inform educational stakeholders in developing policies and school programs that align with family expectations and student needs.